Hydrothermal Valorization of Biosugars with Heterogeneous Catalysts: Advances, Catalyst Deactivation, Mitigation Strategies and Perspectives - Xu, Siyu; Jiang, Yujing; Liu, Juan; Chun‐Ho Lam, Jason; Lin, Richen; Shuai, Li; Shen, Feng; Zhu, Wenlei; Song, Bing (ChemSusChem, 2025)
Sustainable production of valuable biochemicals and biofuels from lignocellulosic biomass necessitates the development of durable and high‐performance catalysts. To assist the next‐stage catalyst design for hydrothermal treatment of biosugars, this paper provides a critical review of (1) recent advances in biosugar hydrothermal valorization using heterogeneous catalysts, (2) the deactivation process of catalysts based on recycling tests of representative biosugar hydrothermal treatments, (3) state‐of‐the‐art understandings of the deactivation mechanisms of heterogeneous catalysts, and (4) strategies for preparing durable catalysts and the regeneration of deactivated catalysts. Based on the review, challenges and perspectives are proposed. Some remarkable achievements in heterogeneous catalysis of biosugars are highlighted. The understanding of catalyst durability needs to be further enhanced based on full examination of the catalytic performance based on the conversion of substrates, the yield, and selectivity of products. Further, a full examination of the physiochemical changes based on multiple characterization techniques is required to eclucidate the relationships between treatment variables and catalyst durability. Collectively, a clear understanding of the relationships between chemical reaction pathways, treatment variables, and the physiochemistry of catalysts is encouraged to be gained to advise the development of heterogeneous catalysts for long‐term and efficient hydrothermal upgrading of biosugars. This graphic illustrates purposefully designing heterogeneous catalysts based on the relationships between reactions, catalysts, and deactivation mechanisms instead of adopting the conventional trial‐and‐error methodology for the hydrothermal valorization of biosugars.